Rolling actions of shoulders and hips in freestyle swimming - Psycharakis, S.; Coleman, S.; Connaboy, C.; Kelly, J.; McCabe, C.; Naemi, R.; Sanders, R. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to determine accurately the magnitude of shoulder roll (SR) and hip roll (HR) in freestyle swimming, to assess the significance of the differences between these parameters and to examine whether they are associated with swimming velocity (V). Six male swimmers of national and international level performed a maximum freestyle swim. One non-breathing stroke cycle was selected for analysis. It was shown that swimmers rolled their shoulders significantly more than their hips. Faster swimming velocities were associated with smaller magnitudes of SR, but no significant correlations were found for V and HR. These results indicated that SR and HR need to be examined separately in freestyle swimming, as the measurement of body roll for the whole trunk does not represent with validity the rolling characteristics of the trunk.